Self-Control sebagai Faktor dalam Menghadapi Fear of Missing Out pada Generasi Z - Zerlina, Audrey; Erlina, Merly (Merpsy Journal, 2025)
Abstract:Fear of Missing Out in this context is defined as the feeling of worry or anxiety when individuals feel left behind from the experiences or information of others, which triggers the desire to stay connected to the activities of others through social media. This study was conducted on 195 social media users. The research method used a quantitative approach with correlational data analysis techniques. Sampling was conducted using non-probability sampling with purposive sampling techniques. Data collection was carried out using several instruments, namely the Fear of Missing Out Scale (FoMOs) and the Brief Self-Control Scale. The results of the study revealed a negative and significant relationship between self-control and FoMO. This means that the higher an individual's self-control ability, the lower the likelihood of experiencing FoMO. Conversely, when self-control is low, the tendency to experience FoMO becomes higher. Therefore, it can be concluded that the hypothesis (Ha) is accepted.